WHEN ARBITRATION AND BANKRUPTCY COLLIDE: REGULATION IN INDONESIA - Kinanti, Fatma Muthia (TANJUNGPURA LAW JOURNAL, 2017)
The growing practice of business in Indonesia directly affects the complexity of business-related disputes. It also often leads to a cross-over between two different legal areas. Settlement of a dispute which have or at least intersect a public nature can become a tricky subject given the contractual nature of arbitration. One of the issues which will then become the basis for this article is the link between arbitration and bankruptcy. More specifically, what if one party in a civil dispute arises from a contract that contain an arbitration clause declared bankrupt? This issue has become so common in the practice, but the jurisprudence shows different views in these matters. The method used in this research is normative juridical research with conceptual approach. The regulations in another countries are also provided to give a comparative value. The conclusion found in this article is that the Core/Non-core Concept adopted in several countries can be applied in Indonesia as the regulation itself supported it.